Phenotypic spectrum of the first Belgian MYBPC3 founder: a large multi-exon deletion with a varying phenotype - Boen, Hanne M.; Alaerts, Maaike; Van Laer, Lut; Saenen, Johan B.; Goovaerts, Inge; Bastianen, Jarl; Koopman, Pieter; Vanduynhoven, Philippe; De Vuyst, Elke; Rosseel, Michael; Heidbuchel, Hein; Van Craenenbroeck, Emeline M.; et al. (Frontiers in Genetics, 2024)
Background Variants in the MYBPC3 gene are a frequent cause of hypertrophic cardiomyopathy (HCM) but display a large phenotypic heterogeneity. Founder mutations are often believed to be more benign as they prevailed despite potential negative selection pressure. We detected a pathogenic variant in MYBPC3 (del exon 23-26) in several probands. We aimed to assess the presence of a common haplotype and to describe the cardiac characteristics, disease severity and long-term outcome of mutation carriers. Methods Probands with HCM caused by a pathogenic deletion of exon 23-26 of MYBPC3 were identified through genetic screening using a gene panel encompassing 59 genes associated with cardiomyopathies in a single genetic center in Belgium. Cascade screening of first-degree relatives was performed, and genotype positive relatives were further phenotyped. Clinical characteristics were collected from probands and relatives. Cardiac outcomes included death, heart transplantation, life-threatening arrhythmia, heart failure hospitalization or septal reduction therapy. Haplotype analysis, using microsatellite markers surrounding MYBPC3, was performed in all index patients to identify a common haplotype. The age of the founder variant was estimated based on the size of the shared haplotype using a linkage-disequilibrium based approach. Results We identified 24 probands with HCM harbouring the MYBPC3 exon 23-26 deletion. Probands were on average 51 ± 16 years old at time of clinical HCM diagnosis and 62 ± 10 years old at time of genetic diagnosis. A common haplotype of 1.19 Mb was identified in all 24 probands, with 19 of the probands sharing a 13.8 Mb haplotype. The founder event was estimated to have happened five generations, or 175–200 years ago, around the year 1830 in central Flanders. Through cascade screening, 59 first-degree relatives were genetically tested, of whom 37 (62.7%) were genotype positive (G+) and 22 (37.3%) genotype negative (G-). They were on average 38 ± 19 years old at time of genetic testing. Subsequent clinical assessment revealed a HCM phenotype in 19 (51.4%) G+ relatives. Probands were older (63 ± 10 vs. 42 ± 21 years; p < 0.001) and had more severe phenotypes than G+ family members, presenting with more symptoms (50% vs. 13.5%; p = 0.002), arrhythmia (41.7% vs. 12.9%, p = 0.014), more overt hypertrophy and left ventricular outflow tract obstruction (43.5% vs. 3.0%; p < 0.001). Male G+ relatives more often had a HCM phenotype (78.6% vs. 34.8%; p = 0.010) and were more severely affected than females. At the age of 50, a penetrance of 78.6% was observed, defined as the presence of HCM in 11 of 14 G+ relatives with age ≥50 years. Overall, 20.3% of all variant carriers developed one of the predefined cardiac outcomes after a median follow-up of 5.5 years with an average age of 50 (±21) years. Conclusion A Belgian founder variant, an exon 23-26 deletion in MYBPC3, was identified in 24 probands and 37 family members. The variant is characterized by a high penetrance of 78.6% at the age of 50 years but has variable phenotypic expression. Adverse outcomes were observed in 20.3% of patients during follow-up.